Men Against the Wall: Graffiti(ed) Masculinities - Lombard, Kara-Jane (Men's Studies Press, 2013)
This paper invokes the categories of the masculine that have been discursively constructed in the historical and social context of hip hop and graffiti culture. The production and performance of graffiti(ed) masculinities are the result of a complex mix that samples notions of class, race, violence, space, commodification, gender, resistance, and violence. Graffiti culture embodies the colonizer’s ideals of a masculinity that is dangerous, aggressive and takes risks, while giving men a medium with which to tell their stories and allowing them to express their emotions. The article argues that graffiti(ed) masculinities are composed of seemingly disparate and complex components that shadow the masculine ideals of the colonizer, of hegemonic masculinity, as well as borrowing from notions of subordinate and resistive masculinities.